Biomehanicheskie osobennostitehniki tolchka shtangiu kvalificirovannyh sportsmenok - Oleshko, V.; Ivanov, A.; Solodkaia, O. (Science in Olympic Sport, 2017)
The paper addresses the problem of the influence of biomechanical characteristics of jerk technique in qualified female weightlifters of different groups of weight categories on their competitive performance. Particular attention is paid to the analysis of biomechanical structure of jerk technique in female athletes from three groups of weight categories, which was documented in the "control" intensity zone (the weight of the barbell was 92-100% of the maximum) during competitive activity under two conditions of the execution of the competitive exercise: successful and unsuccessful. An attempt was made to identify the causes of technical mistakes made by athletes from different weight groups in the execution of the jerk, especially during execution of unfinished competitive exercises, and the influence of biomechanical characteristics on the movement structure of the barbell. There were found significant differences in biomechanical characteristics of the jerk technique in female athletes of different weight categories, most of which are caused by a disturbance of the dynamic and, consequently, kinematic structure of the barbell movement, that indicates the need for its systematic correction.